2016
DOI: 10.1021/acs.chemmater.6b00161
|View full text |Cite
|
Sign up to set email alerts
|

Stratified Micellar Multilayers—Toward Nanostructured Photoreactors

Abstract: Polyelectrolyte multilayers (PEMs) with stratification of the internal structure were assembled from statistical amphiphilic copolyelectrolytes of opposite charges. These polyelectrolytes organize in aqueous solutions into micellar structures with fluoroalkyl and aromatic nanodomains, respectively, that were also preserved after deposition as thin films via layer-by-layer (LbL) electrostatic self-assembly. The unimolecular micelles, formed due to statistical compositions of amphiphilic polyelectrolytes used, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…The concept of the LbL technique was adapted for colloidal particles that serve as removable templates leading to the formation of the capsules with liquid cores [ 32 ]. Such a procedure enables the utilization of macromolecules of complex structure [ 34 ] varying in charge or glass transition [ 35 ] to reach the coatings and capsules of desired functionality [ 36 , 37 ].…”
Section: Fabrication Of Polymer Core-shell Nanocapsulesmentioning
confidence: 99%
“…The concept of the LbL technique was adapted for colloidal particles that serve as removable templates leading to the formation of the capsules with liquid cores [ 32 ]. Such a procedure enables the utilization of macromolecules of complex structure [ 34 ] varying in charge or glass transition [ 35 ] to reach the coatings and capsules of desired functionality [ 36 , 37 ].…”
Section: Fabrication Of Polymer Core-shell Nanocapsulesmentioning
confidence: 99%
“…Furthermore, when a hydrophilic–lipophilic polymer is supplied with a third structural element, it expands the possibilities for the development of self-assembled multi-compartment macromolecules [92,93,94,95,96,97,98,99,100,101,102,103,104]. It often has remarkable effects on the catalytic behavior [92,105,106], the interaction with biological membranes [107,108,109,110], or the transport of active substances [103,109,111,112].…”
Section: From Polymer Amphiphilicity To Polyphilicitymentioning
confidence: 99%
“…In such systems, the shape of adsorbate molecules gives rise to orientation-dependent interactions. Recently, experimental studies of the formation of multilayer structures by amphiphilic molecules have been reported [ 31 , 32 , 33 ]. However, these multilayer structures are not formed via adsorption processes, but rather in the bulk, due to the nature of interparticle interactions in such systems.…”
Section: Introductionmentioning
confidence: 99%